SNAKE ASSEMBLAGE IN AN UNFLOODED FOREST IN WESTERN BRAZILIAN AMAZON - Batista Turci, Luiz Carlos; Machado, Reginaldo Assêncio Machado; Bernarde, Paulo Sérgio Bernarde (South American Journal of Basic Education, Technical and Technological, 2021)
We present data on the natural history of a snake assemblage in the Upper Juruá River (State of Acre, Brazil). We sampled the snakes using time constrained visual search, pitfall traps, and accidental sighting. We collected 179 specimens of 42 species. At night, most snakes were recorded on the vegetation either active (moving or foraging) or resting. In terms of activity time, 49.6% of the species were diurnal, 42% were nocturnal, and 8.2% were active during day and night. Forty-three percent of the snakes were terrestrial, 33% were semi-arboreal and arboreal, 20% were cryptozoic and fossorial and 4% were aquatic. The most common prey utilized by this snake assemblage were lizards (43% of the species), amphibians (32%), mammals (30%), birds (19%) and snakes (13%). The species richness can still be considered to be underestimated, illustrating the need for further surveys and also studies of possible negative impacts of human activities on snake populations.